2018
DOI: 10.3889/oamjms.2018.265
|View full text |Cite
|
Sign up to set email alerts
|

Health Promotion Toolkit: An Approach for Empowering Families Caring For Children with Developmental Disabilities in Tabuk

Abstract: AIM:The study aimed to determine the effects of the health promotion toolkit on empowering families caring for children with developmental disability. It hypothesised that health promotion toolkit would effectively improve families’ empowerment and alleviate parental stress.METHODS:The research design was quasi-experimental. A convenience sample of 30 children with DD and their families enrolled at Shoaa ElAmal Center in Umluj participated. Tools were Health Promotion Assessment Sheet, Family Empowerment Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In our study, the intervention group's care burden lessened. Studies have reported a negative correlation between parental stress and family empowerment ( 41 ). Caregivers can be empowered through informal resources, such as family, friends, and support groups, to reduce the care burden ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the intervention group's care burden lessened. Studies have reported a negative correlation between parental stress and family empowerment ( 41 ). Caregivers can be empowered through informal resources, such as family, friends, and support groups, to reduce the care burden ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of nursing interventions have demonstrated utility in supporting families of children with DD. Health promotion toolkits (e.g., assessment and monitoring guides, education sessions) designed for children with DD can promote family empowerment and relieve stress by supporting parental self-efficacy and self-esteem ( Ghoneim, 2018 ). Nurses can support and empower families affected by childhood DD by employing interventions such as the Family Strengths Oriented Therapeutic Conversation (e.g., developing a nurse-patient-family relationship, welcoming family illness stories and beliefs, recognizing resilience, and offering information), which can improve parents’ quality of life and satisfaction with health care services ( Svavarsdottir et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Education and empowering the mothers during follow up help them not only to cope with their infants, but also enable them to give home care to their infants. Plan of mothers' education is to promote their independency and nurses are responsible for supporting, educating, and enhancing mothers coping with their infant [14] . Provide an educational program for mothers before discharge for increase their knowledge [15] .…”
Section: Introductionmentioning
confidence: 99%